Microcomputer applications - Grauer, Robert T.; Sugrue, Paul K. (New York : McGraw Hill Education, 1989)
Introductory courses that once emphasized the mainframe and BASIC programming now stress the microcomputer and its applications.
Part 1. Computer literacy -- Part 2. Word processing -- Part 3. Spreadsheets -- Part 4. Data management -- Part 5. Advanced topics.
Includes index.
Keywords: MICROCOMPUTERS